Vitamin D ameliorates stress ligand expression elicited by free fatty acids in the hepatic stellate cell line LX-2 - Şeyda SEYDEL,; Anja BEILFUSS,; Alişan KAHRAMAN,; Kıymet AKSOY,; Guido GERKEN,; Hikmet AKKIZ,; Ali CANBAY, (Turkish Journal of Gastroenterology, 2019)
-